ChemInform Abstract: Chemoselective Synthesis of Unsymmetrical Internal Alkynes or Vinyl Sulfones via Palladium‐Catalyzed Cross‐Coupling Reaction of Sodium Sulfinates with Alkynes. Issue 48 (2nd December 2014) - Xu, Yanli; Zhao, Jinwu; Tang, Xiaodong; Wu, Wanqing; Jiang, Huanfeng
Abstract The reaction of ortho‐substituted arylsulfinic acid sodium salts with 3‐phenylpropiolic acid gives β‐keto sulfinones [cf.